2017
DOI: 10.1371/journal.ppat.1006337
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Lassa virus LAMP1 binding site reveals unique determinants not shared by other old world arenaviruses

Abstract: Cell entry of many enveloped viruses occurs by engagement with cellular receptors, followed by internalization into endocytic compartments and pH-induced membrane fusion. A previously unnoticed step of receptor switching was found to be critical during cell entry of two devastating human pathogens: Ebola and Lassa viruses. Our recent studies revealed the functional role of receptor switching to LAMP1 for triggering membrane fusion by Lassa virus and showed the involvement of conserved histidines in this switch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(65 citation statements)
references
References 22 publications
3
62
0
Order By: Relevance
“…Both OW and NW arenaviruses display a glycoprotein complex, GPC, which is composed of a retained stable signal peptide, GP1 attachment glycoprotein, and membrane-anchored GP2 fusion glycoprotein. Structural studies have shown that the arenaviral GP1 presents a compact a/b fold, and the GP2 forms a class I type fusion architecture (Bowden et al 2009;Abraham et al 2010;Igonet et al 2011;Parsy et al 2013;Cohen-Dvashi et al 2015;Mahmutovic et al 2015;Hastie et al 2016Hastie et al , 2017Li et al 2016;Israeli et al 2017;Shimon, Shani, and Diskin 2017;Zeltina et al 2017;Clark et al 2018; Pryce et al 2018) (Fig. 1F).…”
Section: Discrete Structural and Functional States Of The Arenaviral Gp1mentioning
confidence: 99%
“…Both OW and NW arenaviruses display a glycoprotein complex, GPC, which is composed of a retained stable signal peptide, GP1 attachment glycoprotein, and membrane-anchored GP2 fusion glycoprotein. Structural studies have shown that the arenaviral GP1 presents a compact a/b fold, and the GP2 forms a class I type fusion architecture (Bowden et al 2009;Abraham et al 2010;Igonet et al 2011;Parsy et al 2013;Cohen-Dvashi et al 2015;Mahmutovic et al 2015;Hastie et al 2016Hastie et al , 2017Li et al 2016;Israeli et al 2017;Shimon, Shani, and Diskin 2017;Zeltina et al 2017;Clark et al 2018; Pryce et al 2018) (Fig. 1F).…”
Section: Discrete Structural and Functional States Of The Arenaviral Gp1mentioning
confidence: 99%
“…In addition, the conformations of most of the loops that connect the secondary structure elements greatly differ. A prominent β-hairpin 11 , which contributes to the LAMP1 binding site on LASVGP1 12 but is shared by other OW mammarenaviruses that do not utilize LAMP1 during cell entry 12 , is missing in LUJVGP1. Instead, this hairpin is reduced in LUJVGP1 to a short loop that connects α-helix 3 with β-strand 6 similarly to GP1 domains from NW mammarenaviruses ( Fig.…”
Section: Lujvgp1 Adopts a Structure That Resembles The Trimer-associamentioning
confidence: 99%
“…Morogoro virus adopt a characteristic altered conformation 11,12 compared to the trimer-associated native conformation 15 . In the case of LASV, this altered conformation makes it compatible for binding LAMP1 11,17 , and it may further serve for immunological evasion.…”
Section: Interestingly Gp1 Domains From Ow Mammarenaviruses Like Lasmentioning
confidence: 99%
“…Interestingly, LAMP-1 binding site interaction with LASV GP1 has not been shown to be shared by other OW arenaviruses, and was not found in MOPV and LCMV [49]. It seems the LAMP-1 positive co-staining pattern observed in LCMV-infected cells (Fig.…”
Section: Probing Lcmv-arm Versus Lcmv-we Infection With Inhibitor Drugsmentioning
confidence: 89%
“…Binding of LAMP1 is driven by a triad of histidines on the GP1 and that binding of LAMP1 triggers the LASV spike to catalyze membrane fusion by potentiating its response to pH [29,48]. While this histidine triad is conserved among other OW arenaviruses, LAMP-1 utilization has been shown to be specific for LASV, and LAMP1 is not utilized by LCMV or other OW arenaviruses, regardless of α-DG affinity [27,49]. Additionally, recent research has identified that LAMP 1 increases LASV efficiency during entry, and increases the pH of the late endosomes/lysosomes to promote replication [50].…”
Section: The Arenavirus Life Cyclementioning
confidence: 99%